A comparison of plain ropivacaine 0.5% with plain bupivacaine 0.5% in spinal anaesthesia for orthopaedic surgery - Al-Meeri, Nasreldeen Mohamed Mosleh (2006)
INTRODUCTION Bupivacaine is a popular local anaesthetic drug used for spinal anesthesia, it is relatively cardiotoxic and has a longer duration of motor blockade leading to longer discharge time, research for newer local anaesthetic with less cardiotoxicity and minimal motor blockade is aimed. Ropivacaine is a relatively new long-acting local anesthetic used in spinal anaesthesia, which is structurally and pharmacologically closely related to bupivacaine. However, unlike bupivacaine, which is synthesized as a racemic mixture, ropivacaine is synthesized as a pure S (-) enantiomer. This characteristic feature of the drug may contribute to its faster return of motor function than bupivacaine, and with lower risk of cardiotoxicity. METHODOLOGY A double blind randomized clinical trial on 72 ASA grade 1- II patients who were scheduled to undergo orthopedic surgery of the lower limb with duration of operation less than 3 hours were included in the study. These patients received an intrathecal injection of either: 15 mg of 0.5% plain ropivacaine (3 ml), or 15 mg of 0.5% plain bupivacaine (3 ml) for the above procedure. RESULTS The mean onset of sensory block at T12 dermatome was 4 minutes (SD ±3.4) 1n bupivacaine group and in ropivacaine group it was 5.1 minutes (SD ±3.3) (P<0.207). Where as to reach Tl 0 in bupivacaine group was 6.4 minutes (SD ±3.3) and in ropivacaine group reached in 9.3 minutes (SD ±5.2) (P<O.Ol5). Regarding sensory block at T4, 20 patients (55.5%) in bupivacaine group reached this level with mean onset of sensory block in 6.9 minutes (SD ±3.7). Where as only 4 patients (11 %) in ropivacaine group were able to reach the level of T4 in 15 minutes (SD ±4.08) (P<O.OOl). The duration of sensory block was assessed by the patient's first request for analgesia. In bupivacaine group the mean duration of time of sensory block was 5.4 hours (SD ±1.2) and in ropivacaine group it was 6.5 hours (SD ±2.44) (P<0.02). The mean onset of motor block to reach Modified Bromage Score (MBS 1) in bupivacaine group was 1.4 minutes (SD ±0.8) and in ropivacaine group it was 2.1 minutes (SD ±1.5) (P<0.01). And to reach MBS2, in bupivacaine group and in ropivacaine group was 1.6 minutes (SD ±0.9) and 3.0 minutes (SD ±2.0) respectively (P<O.OOl). While to reach MBS3 bupivacaine group was 2.1 minutes (SD ±1.1) and in ropivacaine group it was 3.6 minutes (SD ±1.8) (P<O.OOI). In the bupivacaine group the mean duration of motor block was 4.7 hours (SD ±1.1) and in ropivacaine group was 3.5 hours (SD ±1.4) (P<O.OOl). CONCLUSION Ropivacaine in a dose of 15 mg as 0.5% solution can be used with an acceptable onset of sensory and motor blockade with a longer duration of analgesia and early mobilization for lower limb orthopedic surgery of duration less than three hours and a level of lower than T12 dermatome. Where as to reach Tl 0 in bupivacaine group was 6.4 minutes (SD ±3.3) and in ropivacaine group reached in 9.3 minutes (SD ±5.2) (P<O.Ol5). Regarding sensory block at T4, 20 patients (55.5%) in bupivacaine group reached this level with mean onset of sensory block in 6.9 minutes (SD ±3.7). Where as only 4 patients (11 %) in ropivacaine group were able to reach the level of T4 in 15 minutes (SD ±4.08) (P<O.OOl). The duration of sensory block was assessed by the patient's first request for analgesia. In bupivacaine group the mean duration of time of sensory block was 5.4 hours (SD ±1.2) and in ropivacaine group it was 6.5 hours (SD ±2.44) (P<0.02). The mean onset of motor block to reach Modified Bromage Score (MBS 1) in bupivacaine group was 1.4 minutes (SD ±0.8) and in ropivacaine group it was 2.1 minutes (SD ±1.5) (P<0.01). And to reach MBS2, in bupivacaine group and in ropivacaine group was 1.6 minutes (SD ±0.9) and 3.0 minutes (SD ±2.0) respectively (P<O.OOl). While to reach MBS3 bupivacaine group was 2.1 minutes (SD ±1.1) and in ropivacaine group it was 3.6 minutes (SD ±1.8) (P<O.OOI). In the bupivacaine group the mean duration of motor block was 4.7 hours (SD ±1.1) and in ropivacaine group was 3.5 hours (SD ±1.4) (P<O.OOl). CONCLUSION Ropivacaine in a dose of 15 mg as 0.5% solution can be used with an acceptable onset of sensory and motor blockade with a longer duration of analgesia and early mobilization for lower limb orthopedic surgery of duration less than three hours and a level of lower than T12 dermatome.